2021
DOI: 10.1021/acs.iecr.1c00077
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Application of UiO-66 in Desiccant-Coated Heat Exchanger-Based Desiccant Cooling Systems

Abstract: Dehumidification performance of a high-efficient compact desiccant cooling component named desiccant-coated heat exchanger (DCHE) highly depends on coated desiccant materials. Currently, mesoporous silica gels and salt-supported silica gels have been extensively studied. Silica gels have limited adsorption quantity in the middle relative pressure range, while salt-supported silica gels have potential threat of corrosion. In this work, a metal–organic framework UiO-66 that can achieve good adsorption quantity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…[11,20] In most of AHT applications, porous materials needed superior water adsorption performances within a relative humidity range of 0.05 < P/P 0 < 0.32. [21] However, the water adsorption capacity of UiO-66 reached just 0.1 g/g-0.2 g/g at P/P 0 = 0.3, [11,22] which should be improved. The UiO-66 was modified mainly by introducing functional groups [11,23] and metal ions [24][25][26] to enhance its adsorption performance.…”
Section: Introductionmentioning
confidence: 90%
“…[11,20] In most of AHT applications, porous materials needed superior water adsorption performances within a relative humidity range of 0.05 < P/P 0 < 0.32. [21] However, the water adsorption capacity of UiO-66 reached just 0.1 g/g-0.2 g/g at P/P 0 = 0.3, [11,22] which should be improved. The UiO-66 was modified mainly by introducing functional groups [11,23] and metal ions [24][25][26] to enhance its adsorption performance.…”
Section: Introductionmentioning
confidence: 90%
“…Various studies have reported the utility of silica gel [23,24] zeolites [12,25] metal-organic frameworks [26,27] and activated alumina [28,29] as desiccant coatings in heat exchangers or wheels. The main differences between desiccant coated exchangers (DCHE or desiccant wheels) from conventional energy wheels is need for a dedicated section for regeneration for DCHE, which typically requires a heat source.…”
Section: Introductionmentioning
confidence: 99%